1994
DOI: 10.1093/cvr/28.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Rotational deformation of the canine left ventricle measured by magnetic resonance tagging: effects of catecholamines, ischaemia, and pacing

Abstract: Rotational deformation of the left ventricle is dependent on the pattern of left ventricular activation and the contractile state. That a decrease in the contractile state in one area (by ischaemia) can cause a decrease in rotation in another suggests that this rotation depends on the complex fiber arrangement of the whole ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
3
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 0 publications
5
98
3
3
Order By: Relevance
“…[3][4][5][6][7] Tagged MRI has also been introduced to noninvasively assess LV torsion in various cardiac diseases by measuring LV myocardial deformation using labeling of specific ventricular regions. [8][9][10][11] However, implantation of myocardial markers occurs in a limited number of patients undergoing cardiac surgery or in experimental models, and the influence of the surgery should not be ignored. Both fluoroscopic and MRI analyses require special equipment for image acquisition, the frame rates are also limited, and these methods are time-consuming.…”
Section: Evaluation Of LV Torsionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Tagged MRI has also been introduced to noninvasively assess LV torsion in various cardiac diseases by measuring LV myocardial deformation using labeling of specific ventricular regions. [8][9][10][11] However, implantation of myocardial markers occurs in a limited number of patients undergoing cardiac surgery or in experimental models, and the influence of the surgery should not be ignored. Both fluoroscopic and MRI analyses require special equipment for image acquisition, the frame rates are also limited, and these methods are time-consuming.…”
Section: Evaluation Of LV Torsionmentioning
confidence: 99%
“…18-20 LV torsion of the Endo has been previously reported to be greater than that of the Epi according to tagged MRI analyses, [8][9][10] which suggests that shear occurs between the Endo and Epi (circumferentialradial shear) and this may play an important role in systolic Circ J 2007; 71: 661 -668 (Received December 4, 2006; revised manuscript received January 17, 2007; accepted January 29, 2007 Background The difference in the left ventricular (LV) torsion of the endo-and epicardium (Endo, Epi) with inotropic stimulation and its relation to radial strain (RS) remain unclear. Methods and Results LV basal and apical short-axis images were recorded in 13 normal subjects at rest and during dobutamine infusion (5, 10 g·kg -1 ·min -1 ).…”
mentioning
confidence: 98%
“…Buchalter et al 17 reported that LV rotation was affected regionally during ischemia. Although we tried to include patients with a variety of cardiac pathologies, the studied population was biased toward patients who had an indication for MRI examination.…”
Section: Limitationsmentioning
confidence: 99%
“…[8][9][10] Recently, assessment of LV rotation has become an important approach for quantifying LV function. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, to the best of our knowledge there are no data available to date on the impact of RV volume overload on LV twist in patients with ASD. The recent development of 2-dimensional (D) ultrasound speckle tracking imaging (STI) has allowed LV torsional deformation to be evaluated noninvasively with validation against sonomicrometry and tagged magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%